Obtención de nanocompuestos de polipropileno, etilen-vinil-alcohol y montmorillonita y evaluación de sus propiedades de barrera al oxígeno y vapor de agua (2017)
The aim of this study is to measure the oxygen and water vapor barrier properties of the nanocomposites obtained from the blend of polypropylene, ethylene vinyl alcohol with 32% ethylene and quaternary amine modified montmorillonite. These properties were measured on the basis of the PP / EVOH blend proportion variation at a low and high level. To this end, a co-rotating double-screw extruder was used. The films produced were thermally characterized, their structure was considered and their permeability to oxygen and water vapor was evaluated. It was found that the EVOH in the low level generates a greater degree of crystallinity and the addition of the clay reduces the percentage of crystals in the mixture. Moreover, it was demonstrated by means of the differential scanning calorimetry and X-ray diffraction that no formation of new types of crystals is present, and that the highest crystallinity occurs in the microdomains of polypropylene. Furthermore, a thermogravimetric analysis showed an increase in thermal stability by adding clay to the pure PP and EVOH; however, as the nanocomposites form, a lack of compatibility and lower thermal stability is displayed. With respect to the structure, the exfoliation of the clay in the nanocomposites was achieved. The oxygen transmission rate test did not conform to the norm under which it is governed, thus the effect of the EVOH ratio and the addition of the clay in the oxygen barrier property could not be observed. Conversely, it was found that increased crystallinity through the addition of EVOH improves the water vapor barrier; the low level (10% wt EVOH) has a better barrier than the high one. Also, the addition of the clay improves the water vapor barrier as a result of the increase of the path tortuosity and not by effects of the crystallinity.--Tomado del Formato de Documento de Grado.